De Hemingway au chinois classique : le travail de la langue de l’écrivain taïwanais Wang Wen-hsing - Sandrine Marchand (Continents manuscrits)
Wang Wen-hsing, a well-known Taiwanese contemporary writer, was born in 1939 in Fujian province, Mainland China. In 1946 he moved with his parents to Taiwan. He graduated from National Taiwan University in English Literature and received his MFA at the University of Iowa. He became later professor of English Literature at NTU and remained in his position until retiring in 2005.Except of teaching, all his life is devoted to writing novels in Chinese. During the 1970’s, he is criticized as a Modernist Writer turned towards the United States. Many people said his language was difficult to understand and influenced by English. On the contrary, Wang Wen-hsing himself admits that his model was his French teacher, who was versed in Classical Chinese. Between Classical Chinese, Mandarin, English, French and Minnan dialect, Wang Wen-hsing is creating his own language. We will see first the influence of his English readings, not only on his style but also on his own way of writing, and the possible influence of French and Minnan as well, then we will go through the critics on his two novels and finally we will ask what a genetic methodology on his manuscripts can offer to our reflection on his use of languages in his writings. The use of a syllabary, which appears already in the manuscripts of his first novel, and which will be omnipresent in the second novel: is it another element of strangeness or is it, on the contrary, a tentative to make up refined written language and everyday life’s Mandarin? Why are his novels difficult to read for the common reader? Is it a question of multilingualism or are there some geopolitical reasons in the critics of his writings?